Perbedaan Hasil Pemeriksaan Leukosit Sebelum Dan Sesudah Pembarian Jus Jambu Biji Merah - Aristoteles; Indah Sari (IKesT Muhammadiyah Palembang, 2025)
Background: Leukocytes are blood cells that contain a nucleus, also called white blood cells. Leukocytes are one of the blood components that play a role in protecting against infections caused by viruses, bacteria, or metabolic processes of toxins. There are five types of leukocytes, each of which has a specific function in fighting pathogens, namely neutrophils, eosinophils, basophils, monocytes, and lymphocytes. Leukocytes function as the body's defense system by being transported to cells that experience inflammation such as due to oxidation. Physiological stimulation that can increase the number of leukocytes is exercise, emotion, and extreme temperatures. Red guava is one of the fruits that has many benefits, the benefits of red guava include containing 228 mg/100 grams of vitamin C, rich in folic acid, maintaining the immune system, and preventing anemia. Research Objective: to determine the difference in leukocyte examination results before and after administration of red guava juice. Research Method: Experiment. The study was conducted on March 1, 2023 at Bunda Hospital Palembang and sampling was carried out at the Muhammadiyah Institute of Health Sciences and Technology Palembang, totaling 30 EDTA blood samples with two treatments. Results: the results of the study had an average value of the number of leukocytes before giving red guava juice, namely 6,596 cells/mm3 and the number of leukocytes after giving red guava juice, namely 5,716 cells/mm3. The results of the paired T-test obtained a p value = 0.122. Conclusion: Leukocyte examination can be carried out before or after giving red guava juice.